Nilai-Nilai Pendidikan Jujur Dalam Gagasan Muamalah - Rafifah Qanita; Nailah Assahira; Wismanto Wismanto; Lili Marzila; Rima Junita; Yohana Dwi Putri (Jurnal Budi Pekerti Agama Islam, 2024)
This study discusses the values of honest education in the idea of muamalah. Honesty is a person's attitude when interacting with others both in action and speech. An attitude that becomes the most important ethics in a person when going to meet with others. In this study, this author also provides several explanations, namely the foundation of an honest attitude in muamalah based on the Qur'an and Sunnah, methods that can be done by parents and teachers in applying honest character to their students, the virtues and wisdom of honest attitudes and the impact and attitude of lying. The purpose of this research is to make us aware to be able to apply an honest attitude in everyday life, especially when meeting with others.